Planning of the optimum route of movement of the pilotless flying machine by criterion of the minimum of the general expense of fuel - A. A. Zhuk; V. M. Buloichyk; S. V. Akulich (Системный анализ и прикладная информатика, 2022)
Given article is devoted features of the decision of a problem of planning of a route of a pilotless flying machine (UAV). The decision of a considered problem is offered to be carried out in two consecutive stages. At the first stage calculation of optimum closed route UAV is carried out. Thus as an efficiency indicator the fuel resource, and as criterion of an optimality of a route a minimum of the general expense of fuel is accepted. Efficiency of the received decision is estimated in relation to the known algorithm LinKernighan realised in application Concorde 1.1.  At the second stage by means of the developed algorithm updating of found route UAV taking into account an available stock of fuel is carried out, i.e. The question on returning UAV or after replenishment of a stock of fuel in intermediate point of continuation of flight of the remained sites is solved.